Effects of an Email-Linked Website Intervention on Cancer-Related Nutrition and Lifestyle Risk Factors Among Employees of a Public University - Ang, Yee Kwang (2011)
Epidemiological studies have consistently yielded evidence that healthful nutrition and lifestyle are independently important in the prevention of cancer. Evidence was further established by the World Cancer Research Fund and American Institute for Cancer Research (2007). The internet technology via e-mail and website has been identified as an important channel for health communication and promotion. The objective of this study was to determine the effect of 10-week email-linked website intervention on cancer-related nutrition and lifestyle risk factors among employees of a public university. Ten faculties were randomized to an intervention or control group. The intervention group received weekly emails with hypertext links to a website, http://www.nutrihealth-upm.com, for downloading educational modules for 10 consecutive weeks and individualized phone calls whilst the control group received no weekly emails. Ten educational modules were developed in accordance with the international guidelines for cancer prevention in the Malay language. Employees who were systematically sampled in the selected faculties were recruited with informed consent (n=339). Baseline and post-intervention cancer related nutrition and lifestyle assessments were conducted by using a reliable self-administered questionnaire. Study groups (Intervention, I=134; Control, C=126) completed all assessment at baseline, immediately after intervention (T1), and at 3 months post-intervention (T2). There were no significant baseline differences between the intervention and control groups for any of the socio-demographic and economic, nutrition and lifestyle risk factors (high dietary fat, low fruit and vegetable intake, smoking, alcohol consumption and low physical activity), and psychosocial variables except for perceived benefits for reducing fat intake, and increasing fruit and vegetable intake. At T2, a significant small increase in serving size for fruit and vegetable, total physical activity and walking was observed in the intervention group. A significant improvement in dietary vegetable intake was similarly observed in the control group, but not for physical activity. No significant change on the anthropometric measurements (body weight, waist and hip circumferences, body mass index, and waist-hip ratio) was observed. In addition, the results showed a significant positive change (p<.05) for the total knowledge and subscales (diet, physical activity, weight management, and lifestyle), perception on health status and cancer risk, and psychosocial factors (self-efficacy, perceived benefits and perceived barriers) for dietary fat, fruit and vegetable intake, and physical activity in the intervention group at T1 and T2. However, the change in knowledge and change in psychosocial factors did not significantly correlate with each other as well as with the change in nutrition and lifestyle risk factors. In conclusion, effectiveness of this email-linked website intervention in improving cancer-related knowledge, perception and psychosocial factors may implicate employees to modify health behaviour risk factors although additional elements such as environment and social support are needed to bring about such a positive move. The use of the internet as a means to educate the general public about disease prevention should be maximized as it is a potential avenue for health communication and is increasingly accessible to the adult population.